Дослідження тришарових стін виготовлених за технологією 3Д друку з внутрішнім пінобетонним заповнювачем - Васьків, Іванна Володимирівна; Vaskiv, Ivanna Volodymyrivna (Національний університет "Львівська політехніка", 2024)
У даній роботі розглянуто просторові стінові конструкції, виготовлені методом пошарового 3D-друку з інтегрованим теплоізоляційним прошарком із пінобетону, що мав різні показники щільності. Актуальність дослідження зумовлена зростаючою потребою у сучасних будівельних рішеннях, які поєднують низьку вагу, швидке зведення, достатню міцність і здатність протистояти зовнішнім впливам, зокрема ударного чи вибухового характеру. У ході дослідження було проведено серію експериментальних випробувань, що дали змогу оцінити поведінку таких конструкцій під навантаженням, проаналізувати механізми виникнення тріщин і деформацій у бетонних оболонках, а також визначити ефективність використання пінобетону різної щільності як внутрішнього заповнювача. Навантаження прикладалися до повного руйнування зразків, що дозволило встановити реальні межі їх несучої здатності. У межах дослідження було здійснено аналіз впливу зміни щільності пінобетону (в діапазоні від D150 до D300) на загальні технічні характеристики стінової конструкції. Окремо досліджувався вплив армування на взаємодію між шарами, що дозволило оцінити ступінь покращення спільної роботи матеріалів у межах багатошарової системи. Особливу увагу приділено оцінці стійкості до дії вибухових навантажень — зразки проходили випробування на проникнення уламків та куль, що імітує умови використання конструкцій у сфері захисного будівництва. Також розроблено концепцію захисного громадського простору — «Острівець безпеки», адаптованого до функціонування як у повсякденних умовах, так і в режимах надзвичайних ситуацій. Для підтвердження доцільності впровадження обраної технології здійснено техніко-економічне порівняння з традиційними будівельними методами. Об’єкт дослідження – фізико-механічна поведінка, опір руйнуванню та теплоізоляційні властивості багатошарових друкованих конструкцій Предмет дослідження – тришарові стіни з наповнювачем із пінобетону, надруковані на 3Д принтері. Мета дослідження – оцінити ефективність конструктивної схеми тришарових стін, визначити доцільність їх використання для захисту та енергоефективного будівництва. У результаті дослідження встановлено, що тришарові стіни, виготовлені за технологією 3D-друку з пінобетонним заповненням, демонструють достатню несучу здатність (до 450 кН) і високу теплоізоляцію. Густина пінобетону не мала вирішального впливу на міцність, однак впливала на теплоізоляційні властивості. Армування склопластиковими сітками покращило спільну роботу шарів. Конструкції успішно протидіяли вибуховим та кульовим навантаженням, що підтверджує їхню придатність для використання у захисному та енергоефективному будівництві.

The paper investigates spatial wall elements created by layer-by-layer construction 3D printing with an internal thermal insulation layer of foam concrete of various densities. The relevance of the chosen topic is determined by the need for energy-efficient, quickly assembled structures that combine low weight, sufficient strength, and resistance to external influences, including shock and explosion. A series of physical tests were performed to analyze the behavior of structures under load, study the characteristics of crack formation, deformation processes in concrete shells, and the effectiveness of different types of foam concrete as an internal filler. Loads were applied until complete failure, which allowed establishing the real limits of bearing capacity. The study included an analysis of the impact of changes in the density of foam concrete (D150–D300) on the general characteristics of the wall, as well as determining the degree of influence of reinforcement on the joint operation of the layers. Special attention was paid to resistance to damage by explosive factors - the samples were tested for penetration of fragments and bullets, which simulates the conditions of use of structures in defensive construction. The concept of the "Island of Security" - a protective public module adapted to peaceful and emergency modes of operation - has been developed. A feasibility study of the use of the technology in comparison with traditional methods has been conducted. The object of the study is three-layer walls with foam concrete filler, printed using the 3D method. The subject of the study is the physical and mechanical behavior, resistance to destruction and thermal insulation properties of multilateral printed structures. The purpose of the study is to assess the effectiveness of the structural scheme of three-layer walls, to determine the feasibility of their use for protection and energy-efficient construction. The study found that three-layer walls manufactured using 3D printing technology with foam concrete filling demonstrate sufficient load-bearing capacity (up to 450 kN) and high thermal insulation. The density of foam concrete did not have a decisive effect on strength, but it did affect thermal insulation properties. Reinforcement with fiberglass mesh improved the joint work of the layers. The structures successfully resisted explosive and bullet loads, which confirms their suitability for use in protective and energy-efficient construction.
Research on three-layer walls manufactured using 3D printing technology with internal foam concrete filler
Keywords: 3.192.00.00; 3D-друк у будівництві; пінобетон; багатошарова стінова конструкція; енергоефективне будівництво; міцність конструкцій; теплоізоляційні властивості; ударостійкість; захист від вибуху; дослідні зразки; експериментальне випробування; технологічна ефективність; фізико-механічні характеристики; 3D printing in construction; foam concrete; multilayer wall construction; energy-efficient construction; structural strength; thermal insulation properties; impact resistance; explosion protection; prototypes; experimental testing; technological efficiency; physical and mechanical characteristics. List of used literature sources: 1)Demchyna B.; Vozniuk L.; Surmai M. Testing of the Ribbed Dome Manufactured by 3D Printing // Lecture Notes in Civil Engineering. – Cham : Springer; 2024. – Vol. 438. 2)Paul S.C.; van Zijl G.P.A.G.; Gibson I. 3D printing with cementitious materials — Technologies; challenges; and future directions // Construction and Building Materials. – 2022. 3)ISO/ASTM 52900:2021. Standard Terminology for Additive Manufacturing – General Principles – Terminology. – ISO/ASTM International; 2021. 4)Symonenko V.V. Technologies of construction 3D printing in Ukraine // Bulletin of construction. – 2023. 5)First 3D-printed house in Ukraine built in city of Irpin”; Interfax-Ukraine; July 22; 2024 6)Modern heat-insulating materials: UNIZOL / Materials of the All-Ukrainian Scientific and Practical Conference "Innovations in Construction"; 2023. 7)Foam concrete in modern construction: properties; technologies and prospects for use / Bulletin of Construction. – 2020. 8)Ruan S.; Zhang Z.; Wang X. Application of lightweight foamed concrete in 3D printed multilayer walls // Construction and Building Materials. – 2023. 9)Demchyna B.G.; Lytvynyk O.Ya.; Verba V.B.; Demchyna Kh.B.; Polovko A.P. Structures made of non-autoclaved foam concrete:Prostir-M; 2019.348 p